Benchmarks for the benchmark approach to valuing long-term insurance liabilities: comment on Fergusson & Platen (2023). (20th March 2023) - Bauer, Daniel
Abstract: This article comments on the paper "Less-expensive long-term annuities linked to mortality, cash and equity" by Kevin Fergusson and Eckard Platen, appearing in this issue of the Annals of Actuarial Science . It adds two perspectives to their thought-provoking contribution. The first is a similarity to some recent work in quantitative finance on "deep hedging" that leverages machine learning models to find the cheapest replication strategy for a derivative payoff in a largely model-free setting. The second perspective engages with some of the interesting implications of their approach and draws parallels to literature in asset pricing and macro-finance. These perspectives point to the potential need for more fundamental shifts than the authors of the paper are advertising.